Chronic N-acetylcysteine treatment improves anhedonia and cognition in a mouse model of the schizophrenia prodrome - Bühner, Lukas Marius; Kapanaiah, Sampath K. T.; Kätzel, Dennis (Frontiers in Behavioral Neuroscience, 2022)
Schizophrenia is a severe psychiatric disorder whose neurodevelopmental pathogenesis includes a prodromal phase before its diagnostically decisive - namely psychotic – symptoms are present. This prodrome is characterized by cognitive and affective deficits, and it may constitute a critical time period for an early therapeutic intervention to improve or even prevent further disease development. N-acetylcysteine (NAC) is an easily repurposable compound that has recently shown promise in improving non-psychotic symptoms in patients with established schizophrenia. Its therapeutic mechanism may involve the amelioration of circuit abnormalities like a hyper-glutamatergic state and oxidative stress in cortex which have been proposed to drive the pathogenesis of this disease. However, it is currently unknown to what extent NAC can actually improve prodromal aberrations. To investigate this preclinically, we deployed the cyclin-D2 knockout mouse model (CD2-KO) that shares physiological and behavioural abnormalities with the schizophrenia prodrome, including a hyperactive CA1 region, and cognitive and affective deficits. Applying NAC chronically in drinking water (0.9 g/l) during development (~P22-P70), we found that excessive novelty-induced hyperlocomotion was neither ameliorated during (~P68) nor after (~P75) treatment; similarly, T- working memory (tested after ~P84) was unaffected. However, once chronic NAC treatment was resumed (at approximately P134) in those mice that had received it before, working memory, cognitive flexibility (tested under NAC), and anhedonia (sucrose-preference, tested 1 day after NAC-treatment stopped) were improved in CD2-KO mice. This suggests that chronic NAC treatment may be a therapeutic strategy to improve some cognitive and affective dysfunctions in the schizophrenia prodrome.